The Role of Financial Literacy and Technology Readiness in Encouraging the Use of Fintech for Financial Planning Among Generation Z - Siboro, Sonny Francisco; Ferdiyanto, Yusriel Arief; Frimayasa, Agtovia (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the influence of Technology Readiness and Financial Literacy on Fintech Utilization and Financial Planning, considering the mediating role of Financial Planning. Using the PLS-SEM method via SmartPLS 3 and involving 100 respondents who have actively used fintech services in the past year, the study finds that both Technology Readiness and Financial Literacy have a positive and significant impact on Fintech Utilization and Financial Planning. Individuals with higher technology readiness are more likely to utilize technology-based financial services and have better financial planning capabilities. Similarly, Financial Literacy plays a role in enhancing fintech utilization and improving financial planning skills. Another key finding is that Financial Planning significantly mediates the relationship between Technology Readiness and Fintech Utilization, but it does not mediate the relationship between Financial Literacy and Fintech Utilization, indicating that financial literacy has a more direct impact. The practical implications of this study highlight the need for increasing financial literacy and promoting technology adoption in financial activities, both by fintech service providers and stakeholders in the financial sector. The findings also serve as a reference for future research to explore other factors influencing fintech utilization and financial planning in the digital era.